Inovasi Pendidikan Karakter dalam Mengatasi Learning Loss pada Masa Transisi Pandemi Covid-19 - Rizkia Amalia; Siti Nurbayani; Elly Malihah (Universitas Pendidikan Mandalika, 2023)
This study aims to describe character education innovations in overcoming learning loss during the transition period of the Covid-19 pandemic. This research used a case study method with a qualitative approach. The selection of this informant used a purposive sampling technique. Direct observation, structured interviews, and documentation were used to collect data. Data analysis techniques were used in the stages of data collection, data reduction, data presentation, and conclusion drawing. According to the findings of this study, innovations in overcoming Learning Loss included (1) home visits which aim to learn more about the obstacles students face and to establish cooperation with parents, (2) emergency face-to-face learning to assist students who were unable to do online learning and (3) Assignments in groups that aimed to arouse the spirit of motivation in learning and raise the value of student responsibility.